Performance of all Public Sector Banks with Reference to Micro and Small Enterprises Sector Credit - Vennila, D.; Santhiyavalli, G. (Indian Journal of Research in Capital Markets, 2016)
The micro and small enterprises (MSE) sector has developed into a highly vibrant and dynamic sector of the Indian economy since the last few decades. The sector contributed about 45% of the country's manufacturing output, 40% of total exports of the country, employed about 69 million persons in over 29 million units throughout the country (as per the 12th Five Year Plan), and the sector contributed to 8% of the country's GDP (Annual Report 2013-14, Ministry of MSME, Government of India). In spite of the major contributions to the economy, the sector faces varied challenges such as problems in achieving economies of scale in procuring equipment, raw materials, finances, and consultancy services. Among these challenges, the procurement of finances is considered as a major challenge. The MSE sector primarily relies on bank finance for their business purposes. However, still, availing timely and adequate finances is not hassle free. The Government of India and Reserve Bank of India have been taking enormous steps through Five - Year plans and policy guidelines to boost up finances to this vibrant sector. The Government of India enacted the Micro and Small Enterprises Development (MSMED) Act, 2006 with the aim of ensuring an adequate flow of capital to the MSE sector to keep the sector ever vibrant. With this background, the present study was undertaken to review the performance of all scheduled commercial banks at an all India level with the aim of understanding the growth in the flow of credit to this sector from the year 2000-01 to 2013-14. Every year, all scheduled commercial banks should earmark 40% of their total advances to the priority sector, and the MSE sector is also a part of this priority sector. The study revealed that the total amount of credit outstanding to the MSE sector from all scheduled commercial banks was â‚¹60,319 crores in 2000-01 and it had increased to â‚¹8,46,135 crores in the year 2013-14, registering a compound annual growth rate of 23% during the period of the study. Even though there is a hike in the flow of credit to the MSE sector after the passage of the MSMED Act, the Mann-Whitney U test revealed that statistically, there was no significant difference in the growth rates of credit flow after the passage of the Act.